Impact of Intensive Afforestation Programme on the Rehabilitation of Punjab Shivaliks - Singh, Karam; Kumar, Balbir; Singh, Nirmal (Indian Forester, 1995)
The paper presents the results of intensive afforestation programme on the rehabilitation of Punjab Shivaliks,carried out during 1979-80 to 1987-88 by the Kandi Watershed and Area Development Project (KWADP).